Meeting Asia infrastructure needs. (Key indicators for Asia and the Pacific., 2017)
Developing Asia will need to invest 1.7 trillion per year in infrastructure until 2030 to maintain its growth momentum, tackle poverty, and respond to climate change. The report examines how much the region has been investing in infrastructure and what will likely be needed through 2030. It also analyzes the challenges shaping future infrastructure investment and development.